Motion by crystalline-like mean curvature: A survey - Yoshikazu Giga; Norbert Požár (Bulletin of Mathematical Sciences, 2022)
We consider a class of anisotropic curvature flows called crystalline curvature flows. We present a survey on this class of flows with special emphasis on the well-posedness of its initial value problem.